2019
DOI: 10.1002/ptr.6517
|View full text |Cite
|
Sign up to set email alerts
|

Herbal medicinal products for inflammatory bowel disease: A focus on those assessed in double‐blind randomised controlled trials

Abstract: Inflammatory bowel disease patients frequently use herbal products as complementary or alternative medicines to current pharmacotherapies and obtain information on them mainly from the internet, social media, or unlicensed practitioners. Clinicians should therefore take a more active role and become knowledgeable of the mechanisms of action and potential drug interactions of herbal medicines for which evidence of efficacy is available. The therapeutic efficacy and safety of several herbal medicines have been s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 96 publications
0
28
0
Order By: Relevance
“…Other experiments have shown that Kushen used in vivo can significantly reduce the number of invasive microbial populations in the intestines of mice, thereby lowering animal mortality caused by E. coli and Clostridium perfringens type B. Besides, Kushen was validated to inhibit NK-1R expression, leading to a reduced secretion of inflammatory cytokines such as IL-1β and IL-8 in cells and the promotion of IFN-γ synthesis (Holleran et al, 2020;Ding et al, 2020). Consequently, this produces certain regulatory effects on abnormal immune responses in the intestinal mucosa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other experiments have shown that Kushen used in vivo can significantly reduce the number of invasive microbial populations in the intestines of mice, thereby lowering animal mortality caused by E. coli and Clostridium perfringens type B. Besides, Kushen was validated to inhibit NK-1R expression, leading to a reduced secretion of inflammatory cytokines such as IL-1β and IL-8 in cells and the promotion of IFN-γ synthesis (Holleran et al, 2020;Ding et al, 2020). Consequently, this produces certain regulatory effects on abnormal immune responses in the intestinal mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…Kushen is a kind of Chinese herbal medicine commonly used to treat UC with DHAS that exerts extensive influence in antiinflammatory, immunosuppression, and antibacterial functions (Holleran et al, 2020). Studies have shown that matrine, a major component of Kushen, possesses broad-spectrum antibacterial effects.…”
Section: Discussionmentioning
confidence: 99%
“…As such, patients are usually searching for further effective and safe treatment options and, hence, often turn to CAM. Previous studies have reported a wide range of CAM agents used for IBD [16,17]. A recent study that surveyed 1,286 Austrian patients with IBD reported that 50.7% used CAM at some point during the disease course [18].…”
Section: Discussionmentioning
confidence: 99%
“…Current therapies are limited by increased risks of infection of cancer by loss of clinical bene t. Since the dissatisfaction with conventional medication, complementary and alternative therapies are commonly used in the patient with UC [5,6], including traditional Chinese medicine (TCM), dietary supplements, probiotics, and mind/body interventions [7,8]. Among them, the therapeutic e cacy and safety of several TCM formulas in IBD have been shown in some double-blind randomized controlled trials [9,10].…”
Section: Introductionmentioning
confidence: 99%